China's Foreign Political and Economic Relations : an Unconventional Global Power. - Heilmann, Sebastian (State & Society in East Asia., 2014)
This balanced and thoughtful book presents a thorough analysis of the dynamics of China's foreign political and economic relations. Sebastian Heilmann and Dirk H. Schmidt consider China's view of the world; its foreign policy decision-making process; its major bilateral relations; and key policy issues such as trade and investment, security, human rights, and climate change. The authors also assess how China's often unconventional and hidden activities underlying its global expansion challenge Western predominance. By explicitly addressing controversies and conflicts and providing.